Redescription of the paedomorphic goby Schindleria nigropunctata Fricke & El-Regal 2017 (Teleostei: Gobiidae) from the Red Sea - Ahnelt, Harald (Zootaxa, 2019)
Schindler’s fishes (Schindleria) are extremely paedomorphic and only a few morphological characters are suitable for species delimitation of these tiny fishes. Three of these key morphological characters, the (i) origin of the dorsal fin relative to the anal fin, (ii) number of vertebrae and (iii) coloration, need reinterpretation in a recently described species, Schindleria nigropunctata. To avoid nomenclatorial problems S. nigropunctata is redescribed from the type material. This species is characterized by 16–17 dorsal fin rays, 16 pectoral fin rays, origin of the anal fin ventral to the 8th dorsal fin ray, 37–38 myomeres, a uniform greyish-white colored body (preserved) and a trunk without obvious pigmentation (no black pigment spots). The eyes are dark grey with a silvery cornea. Dorsally on the cornea are blackish melanophores arranged in a sickle-shaped pattern.